The CORALIE study: improving patient education to help new users better understand their oral contraceptive. (2nd September 2016) - de Reilhac, Pia; Plu-Bureau, Geneviève; Serfaty, David; Letombe, Brigitte; Gondry, Jean; Christin-Maitre, Sophie
Abstract: Objectives: Combined oral contraceptives (COCs) are the most widely used contraceptive method in Europe. Paradoxically, rates of unintended pregnancy and abortion are still remarkably high. A lack of knowledge about COCs is often reported to lead to poor adherence, suggesting an unmet need for adequate contraceptive counselling. Our objective was to investigate the impact on the knowledge level of users of a structured approach to deliver contraceptive information for a first COC prescription. Methods: The Oral Contraception Project to Optimise Patient Information (CORALIE) is a multicentre, prospective, randomised study conducted in France between March 2009 and January 2013. The intervention involved providing either an 'essential information' checklist or unstructured counselling to new COC users. The outcome measure was a questionnaire that assessed whether the information provided to the new user by the gynaecologist had been correctly understood. Results: One hundred gynaecologists and an expert committee used the Delphi method to develop an 'essential information' checklist, after which 161 gynaecologists were randomised to two groups. Group I ( n = 81) used the checklist with 324 new COC users and group II ( n = 80) delivered unstructured information to 307 new COC users. The average score for understanding the information delivered during the visit was significantly higher in women in group I than in the women in group II, even after adjustment for age and previous history of pregnancy: 16.48/20 vs 14.27/20 ( p < 0.0001). Conclusion: Delivering structured information for a first COC prescription is beneficial for understanding contraception. Our tool could ultimately contribute to increased adherence and should be investigated in a prospective study of long-term outcomes.